アニオンギャップ開大を契機に診断されたアルカレミアを呈したエチレングリコール中毒の1例(Ethylene glycol poisoning with alkalemia diagnosed by an elevated anion gap: a case report). Issue 2 (18th February 2021) - (Norihiro Watanabe), 渡邉 紀博; (Yoshikazu Hirose), 広瀬 由和; (Yukinori Inoue), 井ノ上 幸典; (Yasuo Hirose), 廣瀬 保夫; (Gen Nakamura), 中村 元; (Wataru Hatano), 波多野 亘; (Yasushi Hori), 堀 寧
ABSTRACT: Ethylene glycol poisoning can cause severe renal, circulatory, respiratory, and central nervous system disorders. Blood gas test commonly show metabolic acidosis which leads to the diagnosis of ethylene glycol poisoning. However, it is often difficult to acquire a medical history from an affected patient. We experienced a case of alkalemia in blood gas analysis upon initial evaluation despite this poisoning. A man in his 40s was transported to our emergency department with disturbed consciousness. Metabolic alkalosis, which was responsible for hypochloremia, was observed. After admission, he was found to have a significant high anion gap, indicating hidden metabolic acidosis. Ethylene glycol poisoning was suspected, and presence of the metabolite glycolic acid was detected by serum analysis. Ethylene glycol poisoning may not show acidemia due to complications. Even in the absence of acidemia, the anion gap should be noted whenever any kind of poisoning is suspected. 要旨: エチレングリコール中毒は重篤な中枢神経障害，循環・呼吸障害，腎障害を来す。中毒患者からの病歴聴取は困難となりやすいが，血液ガス分析では代謝性アシドーシスを呈する例が多く，診断の契機となることも少なくない。われわれは本中毒でありながら，初療時の血液ガス分析でアルカレミアを呈した症例を経験した。40歳代の男性が意識障害で救急搬送された。初療時には低Cl血症，アルカレミアを認めた。入院後，著しいアニオンギャップ開大があったことを契機に，代謝性アシドーシスが隠れていたことが判明した。エチレングリコール中毒を疑い中毒分析を行ったところ，代謝産物であるグリコール酸が検出された。エチレングリコール中毒では，代謝性アシドーシスに併存する代謝性アルカローシスによって，アシデミアを呈さないことがありうる。中毒を疑う場合には，アシデミアを認めない場合にあってもアニオンギャップに注意を払うべきである。